Hardware Implementation of Ensemble Empirical Mode Decomposition for Critical PQ Disturbances Detection - Hukampal S.R.; Mohanty S.R. (My University, 2025)
Hardware resources utilization are of significant concerns for real-time implementation of any signal processing techniques. This paper presents the design and implementation of ensemble empirical mode decomposition (EEMD) based signal processing technique for detection of critical power quality (PQ) disturbances. The complete algorithm is simulated and implemented in Xilinx zynq xc7z020 field programmable gate array (FPGA) board using a higher abstraction level tool of Xilinx system generator (XSG). Real-time performance of the technique is demonstrated on experiment signal from emulator grid connected PV system and further proposed algorithm is validated for signals obtained on IEEE 13 bus PSACD (v4.6) simulation model. The critical PQ disturbance like PQ associated with harmonic frequency components (mode mix) have been considered. In study, the performance of said technique is also compared with other techniques like discrete wavelet transform (DWT) and empirical mode decomposition (EMD). It is found that under the mode mix and noisy scenario; EEMD technique outperforms as compared to DWT and EMD in accurate real-time detection of PQ events. © 2020 IEEE.